A plasma circulating miRNAs profile predicts type 2 diabetes mellitus and prediabetes: from the CORDIOPREV study - Jiménez-Lucena, Rosa; Camargo, Antonio; Alcalá-Diaz, Juan Francisco; Romero-Baldonado, Cristina; Luque, Raúl Miguel; van Ommen, Ben; Delgado-Lista, Javier; Ordovás, Jose María; Pérez-Martínez, Pablo; Rangel-Zúñiga, Oriol Alberto; López-Miranda, Jose (Experimental & molecular medicine, 2018)
We aimed to explore whether changes in circulating levels of miRNAs according to type 2 diabetes mellitus (T2DM) or prediabetes status could be used as biomarkers to evaluate the risk of developing the disease. The study included 462 patients without T2DM at baseline from the CORDIOPREV trial. After a median follow-up of 60 months, 107 of the subjects developed T2DM, 30 developed prediabetes, 223 maintained prediabetes and 78 remained disease-free. Plasma levels of four miRNAs related to insulin signaling and beta-cell function were measured by RT-PCR. We analyzed the relationship between miRNAs levels and insulin signaling and release indexes at baseline and after the follow-up period. The risk of developing disease based on tertiles (T1-T2-T3) of baseline miRNAs levels was evaluated by COX analysis. Thus, we observed higher miR-150 and miR-30a-5p and lower miR-15a and miR-375 baseline levels in subjects with T2DM than in disease-free subjects. Patients with high miR-150 and miR-30a-5p baseline levels had lower disposition index ( p = 0.047 and p = 0.007, respectively). The higher risk of disease was associated with high levels (T3) of miR-150 and miR-30a-5p ( HR T3-T1 = 4.218 and HR T3-T1 = 2.527, respectively) and low levels (T1) of miR-15a and miR-375 ( HR T1-T3 = 3.269 and HR T1-T3 = 1.604, respectively). In conclusion, our study showed that deregulated plasma levels of miR-150 , miR-30a-5p , miR-15a , and miR-375 were observed years before the onset of T2DM and pre-DM and could be used to evaluate the risk of developing the disease, which may improve prediction and prevention among individuals at high risk for T2DM. Metabolic disease: a red flag for diabetes risk Tiny RNA molecules circulating in the blood could give early warning of type 2 diabetes risk. MicroRNAs help regulate the expression of other genes, and recent research has linked irregularities in these molecules to many different diseases. Researchers led by José López Miranda of the University of Córdoba in Spain monitored a cohort of 462 patients for several years to assess how plasma levels of certain microRNAs are deregulated before the onset and progression of diabetes. They observed a striking ‘signature’ of altered expression in four microRNAs for patients who developed diabetes over the course of the study. Intriguingly, patients with markedly elevated blood sugar—state known as prediabetes—exhibited a similar signature, but with more modest alteration in the gene expression levels, indicating that these microRNAs could help clinicians track and prevent disease onset.